2007
DOI: 10.1063/1.2426875
|View full text |Cite
|
Sign up to set email alerts
|

Manometer extension for high pressure measurement: Nuclear quadrupole resonance study of Cu2O with a modified Bridgman anvil cell up to 10 GPa

Abstract: We report (63)Cu nuclear quadrupole resonance (NQR) measurement of Cu(2)O under pressure up to about 10 GPa at low temperatures. Because the lattice parameter of Cu(2)O changes with increasing pressure, the electric field gradient at the Cu site also changes correspondingly with pressure. This enables us to use the Cu(2)O as an in situ manometer for high pressure nuclear magnetic resonance/NQR up to about 9 GPa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…13) Although it should be revealed by additional experimental approaches whether this superconductivity is intrinsic or not, it is clear that the investigation of this compound under pressure is quite important and that the subsequent NMR studies of BaFe 2 As 2 under high pressure requires such high pressure of 10 GPa. The recent development of a high-pressure NMR/NQR technique by the authors' group 14,15) will help provide further insights into our understanding of this interesting iron-based pnictide.…”
Section: )mentioning
confidence: 99%
“…13) Although it should be revealed by additional experimental approaches whether this superconductivity is intrinsic or not, it is clear that the investigation of this compound under pressure is quite important and that the subsequent NMR studies of BaFe 2 As 2 under high pressure requires such high pressure of 10 GPa. The recent development of a high-pressure NMR/NQR technique by the authors' group 14,15) will help provide further insights into our understanding of this interesting iron-based pnictide.…”
Section: )mentioning
confidence: 99%
“…Although superconductivity should be discussed with the data of T dependence of T À1 1 , if superconductivity is induced even at 2.49 GPa, we may roughly expect a sufficient increase in T 1 due to the gap formation of superconductivity. Therefore, we should continue the NMR measurements at P values beyond 3 GPa in order to determine the magnetic phase diagram and ground state of BaFe 2 As 2 under P with a Bridgman anvil cell 17) and a mini cubic anvil apparatus, 18) which are now in progress. The T-P phase diagram of BaFe 2 As 2 determined from resistivity anomalies.…”
Section: )mentioning
confidence: 99%
“…15) Reyes et al have established Cu 2 O-NQR as a suitable manometer in the temperature range 4 -300 K and for the pressure up to 2 GPa. 15) Fukazawa et al have extended the measurements up to 10 GPa at 1.6 K. 2) We found that the T-and P-dependences of 63 Q can be precisely fit to a formula, which is a refined version of the formula used by Wijin and Wildt 16) and by Reyes et al 15) based upon a simple phononic analysis. The Knight shift of 63 Cu shows a very small P-dependence, À10 ppm/GPa, therefore it can be used to determine the field values in the pressure cell during NMR experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few trials have been reported using modified Bridgeman 2,7) cells, moissanite anvil cell (MAC), 8) or diamond anvil cells (DAC), [9][10][11] problems still remain concerning the insufficient sample space, poor hydrostaticity, or inhomogeneity of the magnetic field due to magnetization of the cells. 7,10) In this paper, we report development of a new type of opposedanvil-cell which can be used to generate pressure up to 9 GPa over a volume of 7 mm 3 with the total cell size of 29 mm  41 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation